Pengaruh Penggunaan Canva dan Kreativitas Siswa Terhadap Motivasi Belajar pada Mata Pelajaran Informatika Kelas 9B di SMP Negeri 2 Tugu (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Advancements in digital technology are fostering a more visual, interactive, and creative approach to Informatics education. This study aims to analyze the influence of Canva usage and student creativity on the learning motivation of Grade IX B students in the Informatics subject at SMP Negeri 2 Tugu, examining these effects both individually and simultaneously. The study employs a quantitative approach with an associative research design. The population consisted of 62 Grade IX students, while the sample comprised 31 students from class IX B, selected using purposive sampling. Data regarding Canva usage and learning motivation were collected via questionnaires, whereas student creativity was assessed using observation sheets. The data were analyzed using multiple linear regression with the aid of IBM SPSS Statistics. The results indicate that Canva usage has a significant effect on learning motivation (significance value of 0.002), and student creativity also has a significant effect (significance value of 0.001). Simultaneously, Canva usage and student creativity significantly influence learning motivation (significance value of 0.001). An R-Square value of 0.574 indicates that the regression model—comprising Canva usage and student creativity—explains 57.4% of the variation in learning motivation, while the remaining 42.6% is attributed to factors outside the research model. These findings demonstrate a significant relationship between Canva usage, student creativity, and learning motivation within Informatics instruction.